(untitled) (International journal of medical sciences, 2026)
The pathogenesis of osteoarthritis of the knee (OAH) is interpreted in modern rheumatology as a complex cascade process resulting from the activation of pro-inflammatory mediators (IL-1β, TNF-α) and matrix metalloproteinases (MMP-13). This study analyzes the limitations of traditional drug therapy in restoring joint homeostasis and the therapeutic efficacy of regenerative medicine methods, in particular autologous plasma (PRP) and stromal vascular fraction (SVF) at the molecular level. The results obtained provide scientific justification for the possibility of modifying the pathological process at early stages and inhibiting chondrocyte apoptosis.